Exploring the Relationship between Tobacco Consumption and Food Consumption - Novaldi Dwi Purnama; Ajeng Septia Mutiara; Irgiana Faturohman; Muhammad Din Fahmi Rahman; Vita Karima (Prosiding Industrial Research Workshop and National Seminar, 2018)
Many people assume that cigarette consumption absorbs substantial household expenditures that affect thepurchase of other food items for consumption. This study aims to evaluate whether there is a relationshipbetween people spending on cigarettes with people expenditure on food. The data used is the average per capitamonthly expenditure in 2013-2017. This data is obtained from data publication of Badan Pusat Statistik (BPS).The method used in this research is correlation analysis. The result shows that the expenditure on cigarettes hasa significant relationship with some foodstuffs. This finding suggests that some of the foodstuffs are not theprimary consumption of food. This result occurs most likely due to indicates that the increasing people's income.